3D ToF‐SIMS view of interfacial diffusion between Cr2AlC coating and zircaloy substrate. (21st November 2019) - Zhang, Lei; Dai, Chunli; Zhang, Jie
Abstract : A diffused interface between a ceramic coating and a metallic substrate is expected to signify a more solid bonding. In addition to depth profiling, a novel 3D view and imaging approach based on ToF‐SIMS analysis was developed to investigate the diffused species around the interface. The diffusion of Al species in a Cr2 AlC ceramic coating and Zircaloy substrate system was investigated in both the as‐deposited and postannealed states. In terms of the 3D view and imaging of CsAl + after Gaussian convolution, Al species visibly diffused into the substrate after annealing at 800°C for only 5 minutes compared with that in the as‐deposited sample.